ChemInform Abstract: π‐Expanded Coumarins: Synthesis, Optical Properties and Applications. Issue 19 (May 2015) - Tasior, Mariusz; Kim, Dokyoung; Singha, Subhankar; Krzeszewski, Maciej; Ahn, Kyo Han; Gryko, Daniel T.
Abstract Review: 179 refs.